2021
DOI: 10.1371/journal.pone.0242205
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of GeneXpert in tuberculosis–HIV co–infected patients at Asella Teaching and Referral Hospital, Southeastern Ethiopia: A cross sectional study

Abstract: Background GeneXpert is a new introduction in the diagnostic modality to fight tuberculosis (TB) among people living with HIV (PLHIV) under the program of intensified TB case finding. This study aimed to evaluate the diagnostic performance of GeneXpert under the program of intensified TB cases finding among PLHIV. Methods Cross-sectional study was conducted by recruiting individuals attending an HIV clinic from February 2018 to January 2019. Data on clinical parameters were collected using a standardized too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…And this is typical to the finding of the study from north-western part of Ethiopia and other multicenter studies [17,18,22,21]. Also congruent with study by Abebe et al [23]. However, the study finding reported by Habte et al indicated "additional TB case detection of GeneXpert among smear AFB negative cases was 64.3%" [13], which was higher than our finding while the report from Cochrane review and meta-analysis by Steingart and his collogues, and studies from other areas were in the range of quarter which were lower than our results [19,14,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…And this is typical to the finding of the study from north-western part of Ethiopia and other multicenter studies [17,18,22,21]. Also congruent with study by Abebe et al [23]. However, the study finding reported by Habte et al indicated "additional TB case detection of GeneXpert among smear AFB negative cases was 64.3%" [13], which was higher than our finding while the report from Cochrane review and meta-analysis by Steingart and his collogues, and studies from other areas were in the range of quarter which were lower than our results [19,14,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…18 The GenExpert TB diagnosis technology has increased early diagnosis of TB in HIV positives and increased survival in HIV+TB coinfection. 30 Ethiopia adopted and scaled up GenExpert diagnosis technology since 2014. 31…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the present study are that, although this comparison models a common and emblematic differential diagnosis, the back-to-back comparison of disseminated histoplasmosis and tuberculosis is reductive and falsely dichotomizes real clinical situations with advanced HIV, where other differential diagnoses may be evoked. The diagnosis of disseminated histoplasmosis and tuberculosis relied on microbiology, the gold standard, but we now know that the sensitivity of these methods is lower than other methods of antigen testing for disseminated histoplasmosis or Gene Xpert for tuberculosis [22]. Therefore, perhaps there are a number of more difficult diagnoses that are not captured by this model.…”
Section: Discussionmentioning
confidence: 99%